Treatment of ACL injury in a professional soccer player during COVID-19 lockdown - Molina, I.; Muñoz, A.; Linde, X. (Apunts Medicina de l'Esport, 2022)
Anterior Cruciate Ligament (ACL) injuries stand out as the most severe in sports such as soccer. This study presents the rehabilitation process of a professional soccer player who suffered a total ACL tear. It details the treatment performed after the surgical intervention and all the adaptations that had to be applied in the rehabilitation process due to the lockdown period established at the beginning of the COVID-19 pandemic. During the period comprised between weeks 9 and 21 post-surgery, the rehabilitation treatment was carried out virtually, adapting the actions, work environment and equipment used. Despite the limitations it entailed, the virtual format and the adaptations in the treatment allowed the rehabilitation process to continue, fulfilling all the pre-established objectives and deadlines with a consequent satisfactory and safe return to competitive sport. After carrying out a bibliographic research, no clinical cases have been found regarding the adaptation of the rehabilitation process of an ACL reconstruction in a professional soccer player during the COVID-19 lockdown.